Plasma Exosomal hsa_circ_0015286 as a Potential Diagnostic and Prognostic Biomarker for Gastric Cancer - Peiming Zheng; Huijie Gao; Xuanhu Xie; Peipei Lu (Frontiers Media S.A., 2022)
Circular RNA (circRNA) is stable and abundant in exosomes as a potential biomarker for the diagnosis and prognosis of tumor. In this study, cancer specific exosomal circRNAs were identified through circRNA microarray, and 58 circRNAs were significantly upregulated in cancer cells derived exosomes. Then 60 patients with newly diagnosed gastric cancer (GC), 30 chronic gastritis patients and 30 healthy subjects were enrolled for further clinical validation. We detected that hsa_circ_0015286 was remarkably highly expressed in GC tissue, plasma and cancer cells compared with normal controls. Results of ROC curve analysis showed that the area under curve (AUC) of hsa_circ_0015286, CEA and CA 19-9 was 0.778, 0.673, and 0.665, respectively. The combined detection of three indicators had the highest AUC (0.843). Exosomal hsa_circ_0015286 expression was closely associated with tumor size, TNM stage and lymph node metastasis. The expression level of exosomal hsa_circ_0015286 in GC patients decreased significantly after surgery. Overall survival of patients with low hsa_circ_0015286 expression was longer than those with high expression. Our data demonstrated that exosomal hsa_circ_0015286 might be a promising noninvasive biomarker for the diagnosis and prognosis evaluation of GC.